2018
DOI: 10.2741/s514
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of Asiatic acid in aluminium chloride induced rat model of Alzheimer rsquo s disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia, characterized by memory loss, cognitive impairment and personality disorders accompanied by diffuse structural abnormalities in the brain of elderly people. The current investigation explored the neuroprotective potential of asiatic acid (AA), a natural triterpene of on aluminium chloride (AlCl) induced rat model of AD. Oral administration of AlCl (100 mg/kg b.w.) for 42 days significantly elevated the levels of Al, activity of acetyl cholinesterase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 43 publications
(44 reference statements)
2
21
0
Order By: Relevance
“…Regarding adrenaline, the present results go with the previous studies, which stated that AD patients have an exhibited loss of LC neuronal cells, reducing to as low as 70% in the rostral nuclei leading to reduced limbic and cortical epinephrine and norepinephrine levels (Gannon et al, 2015). Some clinics in the USA are already using adrenaline as a therapeutic option in the case of AD (Qadir et al, 2014). The use of adrenergic agonists in combination with cholinergic drugs may increase cognitive function and delays the adverse cognitive degeneracy effects associated with progressive geriatric AD (Giorgi et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding adrenaline, the present results go with the previous studies, which stated that AD patients have an exhibited loss of LC neuronal cells, reducing to as low as 70% in the rostral nuclei leading to reduced limbic and cortical epinephrine and norepinephrine levels (Gannon et al, 2015). Some clinics in the USA are already using adrenaline as a therapeutic option in the case of AD (Qadir et al, 2014). The use of adrenergic agonists in combination with cholinergic drugs may increase cognitive function and delays the adverse cognitive degeneracy effects associated with progressive geriatric AD (Giorgi et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…As stated by the "World Alzheimer Report 2018" (Rusek et al, 2019), there is a new case discovered every 3 seconds, mostly in low-and middle-income nations. In the present study, AD was induced in Wistar rats by AlCl 3 at a dose of 100 mg/kg (Rather et al, 2018). This is the maximum level of aluminum allowable in occupational aluminum toxicity and dialysis encephalopathy (Justin et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…AA derivatives have been shown to counteract glutamate-induced excitotoxicity in nerve cells (Lee et al ., 2000), while asiaticoside derivatives can antagonize β-amyloid-induced nerve damage (Jew et al ., 2010; Mook-Jung et al ., 2015). Furthermore, AA shows neuroprotective effects against aluminum-induced neuronal toxicity in vivo and in vitro (Ahmad et al ., 2018a, 2018b). Xiong has shown that rotenone or H 2 O 2 can reduce the mitochondrial membrane potential (MMP) of SH-SY5Y DA cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported the efficacy of an essential oil Z-ligustilide (Z-LIG) extracted from umbelliferous plants, which showed reduced levels of intracellular ROS and regulated the apoptosis in A β -induced toxicity in PC12 cells [ 98 ]. Moreover, it manifested promising results in protecting against neurotoxicity via the activation of PI3K/Akt and the regulation of the p38 MAPK pathway in differentiated PC12 and SHSY5Y neuroblastoma cells [ 98 , 99 ].…”
Section: The Baseline Of Neuroinflammation In Admentioning
confidence: 99%